Fenomena Gig-tripping pada Generasi Z dan Dampaknya terhadap Multiplier Effect Pariwisata - Abdul Khalim; Annisaa Eka Warliati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The phenomenon of gig-tripping reflects a shift in travel behavior among Generation Z, where attending concerts and music festivals has become the primary motivation for travel. The increasing number of events and the growing interest in experience-based activities have positioned events as drivers of tourism mobility with the potential to generate tourism multiplier effects. However, studies examining gig-tripping as a tourism travel behavior and its relationship with the tourism multiplier effect remain limited. This study aims to analyze the gig-tripping phenomenon among Generation Z and its implications for the tourism multiplier effect. The study employed an Exploratory Sequential Mixed Method approach, beginning with in-depth interviews followed by questionnaire distribution. Data were analyzed using thematic analysis and descriptive statistics, while data integration was conducted through connecting and merging approaches. The findings reveal that gig-tripping is influenced by artist appeal, experiential factors, and social media, and has evolved into an integrated tourism activity involving accommodation, culinary experiences, transportation, and tourist visits. This travel pattern generates spending across multiple sectors, indicating the occurrence of a tourism multiplier effect. The novelty of this study lies in integrating gig-tripping, derived tourism activities, and the multiplier effect into a single mixed-method conceptual model: gig-tripping → tourism activities → multiplier effect, thereby enriching the study of event tourism among Generation Z.